Isolation and characterization of cytotoxic and insulin-releasing components from the venom of the black-necked spitting cobra Naja nigricollis (Elapidae). (June 2020) - Conlon, J.M.; Attoub, Samir; Musale, Vishal; Leprince, Jérôme; Casewell, Nicholas R.; Sanz, Libia; Calvete, Juan J.
Abstract: Four peptides with cytotoxic activity against BRIN-BD11 rat clonal β-cells were purified from the venom of the black-necked spitting cobra Naja nigricollis using reversed-phase HPLC. The peptides were identified as members of the three-finger superfamily of snake toxins by ESI-MS/MS sequencing of tryptic peptides. The most potent peptide (cytotoxin-1N) showed strong cytotoxic activity against three human tumor-derived cell lines (LC50 = 0.8 ± 0.2 μM for A549 non-small cell lung adenocarcinoma cells; LC50 = 7 ± 1 μM for MDA-MB-231 breast adenocarcinoma cells; and LC50 = 9 ± 1 μM for HT-29 colorectal adenocarcinoma cells). However, all the peptides were to varying degrees cytotoxic against HUVEC human umbilical vein endothelial cells (LC50 in the range 2–22 μM) and cytotoxin-2N was moderately hemolytic (LC50 = 45 ± 3 μM against mouse erythrocytes). The lack of differential activity against cells derived from non-neoplastic tissue limits their potential for development into anti-cancer agents. In addition, two proteins in the venom, identified as isoforms of phospholipase A2, effectively stimulated insulin release from BRIN-BD11 cells (an approximately 6-fold increase in rate compared with 5.6 mM glucose alone) at a concentration (1 μM) that was not cytotoxic to the cells suggesting possible application in therapy for Type 2 diabetes. Graphical abstract: Image 1 Highlights: Four members of the three-finger superfamily of toxins were isolated from N. nigricollis venom. All peptides were cytotoxic to human tumor-derived cells. The peptides were also cytotoxic to non-neoplastic HUVEC cells. Two isoforms of phospholipase A2 effectively stimulated insulin release from rat clonal β-cells.